Habitat Selection and Mating Success in a Mustelid - Thierry Lodé (International Journal of Zoology)
Habitat selection remains a poorly understood ecological process, but relating mating behaviour to pattern of habitat selection constitutes a fundamental issue both in evolutionary ecology and in biological conservation. From radiotelemetry protocol, habitat-induced variations in mating success were investigated in a solitary mustelid carnivore, the European polecat Mustela putorius. Selection for marshy habitat was regarded as adaptive in that mating success was found greater using marches than other habitats. Males consorted with 1.3 females, revealing a low polygyny rate. Pregnant or lactating females selectively shifted to deciduous woods. That some habitat types may favour a good reproduction forms a key factor for species conservation and environmental management. Nevertheless, such as in various vertebrates, habitat requirements seem to be based on simple broad features of habitat, suggesting that habitat avoidance rather than habitat preference can explain polecat habitat predilection.